Tick-borne microorganisms in Amblyomma tigrinum (Acari: Ixodidae) from the Patagonian region of Argentina - Winter, Marina; Sebastian, Patrick; Tarragona, Evelina Luisa; Flores, Fernando Sebastián; Abate, Sergio Damián; Nava, Santiago (Springer Link, 2024)
This study presents the results of the molecular detection of tick-borne microorganisms in Amblyomma tigrinum Koch collected near the city of Viedma, Río Negro, Argentina. Ticks were collected in their non-parasitic stage, on pet dogs and on Lycalopex gymnocercus (Pampa fox). Also, six tick samples from humans were analyzed. All ticks were morphologically identified to species level and genomic DNA was extracted. The DNA samples were examined by end point PCR assays to amplified DNA of Anaplasma sp., Babesia sp., Ehrlichia sp., Rickettsia sp. and Theileria sp. Although all tested DNA samples from the collected ticks resulted negative to the detection of Piroplasmida and Rickettsia spp., 16 samples (16.5%, including all hosts) were positive in the 16S rDNA gene PCR that detects bacteria from the Anaplasmataceae family. Phylogenetic analysis of seven obtained partial sequences resulted in the identification of three bacteria: two Ehrlichia spp. (related to Ehrlichia sp. strain Iberá and strain Viedma) and Candidatus Anaplasma boleense. The latter finding represents the first detection of this novel Candidatus species in A. tigrinum. Based on the results of this study, it must be assumed that the diversity of bacteria of the Anaplasmataceae family in Argentina is greater than previously thought, and that these bacteria can infect a wide range of domestic and wild animals.